KEKERASAN DALAM RUMAH TANGGA: ANGIN PUTING BELIUNG BAGI HIDUP BERKELUARGA - Utama, Ignatius L. Madya (UNIKA Santo Thomas, 2022)
Christians who got married want to have a happy family life. They also want their family life become a sacrament. Yet, their dreams do not always come true. One of the obstacles that prevent their dreams become a reality is domestic violence that takes place in their family life. On the one hand, the ones doing the violence sometimes even justify their behavior by quoting some teachings from the Scriptures and other Church’s documents. Other factor that supports domestic violence is patriarchical and kyriarchical culture. On the other hand, the life of Jesus, the practice of early Christian communities, as well as other teachings of the Church, especially since the second Vatican Council, challenge us to eracidicate domestic violence as a very serious threat for a happy family life.